An AC impedance spectroscopy study of the freezing-thawing durability of Wollastonite micro-fibre reinforced cement paste. - Sato, Taijiro. (University of Ottawa (Canada), 2002)
The AC impedance spectroscopy (ACIS) is an electrochemical technique used to characterize materials in various research fields owing to its non-destructive nature. The ACIS, accordingly, appears to have a potential as a non-destructive technique to investigate the durability of cement paste. An understanding of the mechanism of frost action occurring within cement paste, a key binding component of concrete, is necessary to improve the durability of concrete with respect to freezing and thawing, particularly where the winter is severe. In addition, the research on the effectiveness of the wollastonite micro-fibres, a cost-effective naturally occurring calcium silicate, as a reinforcing material to improve the durability of cement paste is demanded due to worldwide concerns of material shortages. Three primary objectives in this study are to further the understanding of the mechanism of frost action within cement paste subjected to freezing and thawing, to investigate the potential of the ACIS as a new technique to determine the durability of cement paste with respect to freezing and thawing and to investigate the durability of the wollastonite micro-fibre reinforced cement paste to freezing and thawing. (Abstract shortened by UMI.)
Keywords: Engineering, Civil.